"Al-Mich" Alojzy Michalak Medalierstwo 1972-2002. ([S.l. : s.n.], 2002)
Plakat wystawy, która miała miejsce w Muzeum Archeologicznym w Gdańsku w grudniu 2002 r.
Keywords: Michalak, Alojzy; Medalierzy -- Polska -- Gdańsk -- 1990-.